2019
DOI: 10.7717/peerj.6637
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hydrogen production from Chlorella sp. biomass by acid-thermal pretreatment

Abstract: Background Owing to the high growth rate, high protein and carbohydrate contents, and an ability to grow autotrophically, microalgal biomass is regarded as a promising feedstock for fermentative hydrogen production. However, the rigid cell wall of microalgae impedes efficient hydrolysis of the biomass, resulting in low availability of assimilable nutrients and, consequently, low hydrogen production. Therefore, pretreatment of the biomass is necessary in order to achieve higher hydrogen yield (HY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Effect of acid hydrolysis on total carbohydrates and total reduced sugar content Giang et al (2019) showed that the acid concentration is a limiting factor that can impair microalgal biomass sacchari cation in the autoclave. The total carbohydrate yields were increased with increasing acid concentration during the hydrolysis processes with H 2 SO 4 pre-treatment in the autoclave at 121 °C for 15 min as shown in gure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of acid hydrolysis on total carbohydrates and total reduced sugar content Giang et al (2019) showed that the acid concentration is a limiting factor that can impair microalgal biomass sacchari cation in the autoclave. The total carbohydrate yields were increased with increasing acid concentration during the hydrolysis processes with H 2 SO 4 pre-treatment in the autoclave at 121 °C for 15 min as shown in gure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier research reports have established the Chlorella c ell wall to be composed of an outer cell wall formed of algaenan and a thinner microfibrillar wall composed of cellulose and chitin-like glycan amino sugars [ 54 ]. Substantial research reports have also evidenced the Chlorella cell wall disruption brought forth by acid wash treatments as a phenomenon caused by the interaction of H + ions of acids with the glycosidic bonds of cell wall components [ 55 ]. This might have caused the severe damage to cell wall apparent herein under the increased acid concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…C. vulgaris has been widely reported as the photolytic and photofermentative H 2 -producing microalgal species. The purity of the strain was maintained and checked microscopically during the culturing, which was uncontaminated at the time of harvesting. The strains were suspended in the recommended Z -medium at pH 7, which contained all of the supplementary nutrients for microalgae to grow, as shown in the recipe in the Supporting Information (Table S1).…”
Section: Methodsmentioning
confidence: 99%